172k views
4 votes
Select the correct answer What are the roots of this equation ? x ^ 2 - 2x + 3 = 0

A. 1 +/- I square root 2

B. -1 +/- i square root 2

C. -2 +/- I square root 2

D. 2 +/- i square root 2

Select the correct answer What are the roots of this equation ? x ^ 2 - 2x + 3 = 0 A-example-1

1 Answer

3 votes

Answer: A. x = 1 ± i√2

Explanation:

The given quadratic equation is expressed as

x² - 2x + 3 = 0

The equation is already in the standard form of ax² + bx + c

The general formula for solving quadratic equations is expressed as

x = [- b ± √(b² - 4ac)]/2a

From the equation given,

a = 1

b = - 2

c = 3

Therefore,

x = [- - 2 ± √(- 2² - 4 × 1 × 3)]/2 × 1

x = [2 ± √(4 - 12)]/2

x = [2 ± √- 8]/2

x = 2/2 ± (2i√2)/2

x = 1 ± i√2

User Oenotria
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.